Systemic Vascular Dysregulation May Be Associated With Lower Peripapillary Vessel Density in Non-glaucomatous Healthy Eyes: A Prospective Cross-Sectional Study - Guo, Yiqin; Sun, Yunxiao; Liu, Haoran; Cao, Kai; Wang, Ningli (Frontiers in Medicine, 2021)
Objective: To determine whether systemic vascular dysregulation (SVD) evaluated by nailfold capillaroscope and Flammer Syndrome Questionnaire (FSQ) affects retinal peripapillary microcirculation in non-glaucomatous healthy eyes at steady status. Methods: 120 healthy eyes from 63 non-glaucomatous subjects underwent Optical coherence tomography angiography (OCTA) after a rest of 30 minutes. Average retinal peripapillary capillary (RPC) vessel density (VD) and sectoral VD were automatically calculated, and peripapillary retinal nerve fiber layer thickness (RNFLT) was measured. Vasospastic diathesis was assessed using Flammer Syndrome Questionnaire (FSQ). Cold provocation test (CPT) was performed using nail-fold capillaroscope after OCTA. Positive CPT and a score of FSQ higher than 20% were necessary to determine a subject with SVD. Systemic and ocular parameters were compared between subjects with and without SVD. Results: In this study, heart rate (p =0.042), ocular perfusion pressure (p = 0.014) and average RPC vessel density (p =0.046) was significantly different between subjects with and without SVD determined by the combination of CPT and FSQ. Generalized estimation equation(GEE) showed lower VD was significantly associated with longer axial length (β = -0.352, p =0.001), thinner peripapillary retinal nerve fiber layer thickness (RNFLT) (β = 0.296, p <0.001), SVD determined by CPT and FSQ (β = 0.617, p =0.003) and high blood pressure (β = -0.879, p <0.001). In the superotemporal sector, multivariate model showed only SVD was associated with RPC vessel density (β = -0.811, p <0.001). Conclusion: In subjects with SVD and non-glaucomatous healthy eyes, lower RPC vessel density in the superotemporal sector was observed. SVD determined by CPT and FSQ was significantly associated with attenuated retinal peripapillary microcirculation. Studies on ocular diseases relevant to vasospasms should consider the effects of SVD on the retinal peripapillary capillaries.